Are Women Opting Out? A Mixed Methods Study of Women Patrol Officers' Promotional Aspirations. (December 2021) - Todak, Natalie; Leban, Lindsay; Hixon, Benjamin
Using national survey and interview data from women patrol officers in the United States, we assess whether women are underrepresented in the upper ranks of policing because they are self-selecting out of promotions. With only 42% of the survey sample reporting a desire to promote, we indeed find evidence that many policewomen are either delaying or forgoing promotions. Among those who were eligible for promotion, the most common reasons given for waiting to promote were the desire to keep one's current shift and to gain more experience. Based on our findings, we offer recommendations for reducing gendered barriers to promotion and increasing gender diversity in the upper ranks of law enforcement.